PENERAPAN SISTEM MANAJEMEN KESEHATAN DAN KESELEMATAN KERJA PADA PTPN VII PADANG PELAWI SUKARAJA SELUMA - Mualim, Mualim; yusmidiarti, yusmidiarti (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
The latest regulation in Indonesia on Work Safety and Health Management System(SMK3) is Indonesian Republic Goverment Regulation No. 50 of 2012, explained that the currenttrade globalization impact very tight competition in all aspects, especially for personnelwork, one of which requires protection of work safety and health management system. SMK3implementation under Regulation No. 50 of 2012 had not been evaluated. This study aimed toimplement of safety and health management systems work by Indonesian Republic GovermentRegulation No. 50 of 2012 in PTPN VII Sukaraja Seluma district. This research was a qualitativeresearch with observational approach using documentary study of the application ofSMK3 through primary and secondary data. The sample in this study was derived from thethree directors and the workforce amounted to 30 workers. The instruments those used inthis study were guidelines depth interview and questionnaire. Data analyzed by triangulation.PTPN VII Padang Pelawi Sukaraja has conducted an initial review to identify potential hazardssuch as giving understanding to cope with all workers on the potential dangers that may occurwhether caused by physical, chemical, ergonomic, radiation, biological and psychologicalthat may injure and hurt at work, the use of APD in accordance with the following procedures assessmentand risk control by technical or engineering controls